The Development and Implementation of Lesson Plan in the Teaching of English at SMA Ar Rohmah Dau - Muklas Muklas (Graduate Program, University of Islam Malang, 2021)
The research analyzed the development and implementation of lesson plan in the teaching of English at SMA AROHMAH DAU. The research expounded the process and steps in developing lesson plan and the difficulties faced by teacher in implementing the lesson plan in the process of teaching and learning activity. The subject of this research were the first-class English teacher at SMA AR-ROHMAH DAU.The objectives of the research are to investigate how the English teacher develops the lesson plan and to investigate the difficulties faced by the English teacher in implementing the lesson plan.The method of the research is qualitative to analyze the data. The technique of collecting data is documentation studies and interview with the first-class English teacher and interview the teacher with some questions.The findings of the research indicated that, firstly, the first-class English teacher has some steps to develop lesson plan. Those are identifying the learning objectives, planning the specific learning activities, planning to assess student’s understanding, planning to sequence the lesson in an engaging and meaningful manner, creating a realistic timeline, planning for a lesson closure, modifying the used teaching-method, combining the motivation section inside, maximizing the sophisticated technology toward the implemented lesson plan, and evaluating the process of implementation of lesson plan. Second, the difficulties faced by the teacher in implementing the lesson plan are controlling the students, measuring the quality of the student’s capacity, noisy condition and lack of time that tend to happen when the process of teaching-learning activity has been done yet.